Rhythm of carbon and nitrogen fixation in unicellular cyanobacteria under turbulent and highly aerobic conditions. Issue 9 (7th April 2013) - Krishnakumar, S.; Gaudana, Sandeep B.; Viswanathan, Ganesh A.; Pakrasi, Himadri B.; Wangikar, Pramod P.
Abstract Nitrogen fixing cyanobacteria are being increasingly explored for nitrogenase‐dependent hydrogen production. Commercial success however will depend on the ability to grow these cultures at high cell densities. Photo‐limitation at high cell densities leads to hindered photoautotrophic growth while turbulent conditions, which simulate flashing light effect, can lead to oxygen toxicity to the nitrogenase enzyme. Cyanothece sp. strain ATCC 51142, a known hydrogen producer, is reported to grow and fix nitrogen under moderately oxic conditions in shake flasks. In this study, we explore the growth and nitrogen fixing potential of this organism under turbulent conditions with volumetric oxygen mass transfer coefficient (KLa) values that are up to 20‐times greater than in shake flasks. In a stirred vessel, the organism grows well in turbulent regime possibly due to a simulated flashing light effect with optimal growth at Reynolds number of approximately 35, 000. A respiratory burst lasting for about 4 h creates anoxic conditions intracellularly with near saturating levels of dissolved oxygen in the extracellular medium. This is concomitant with complete exhaustion of intracellular glycogen storage and upregulation of nifH and nifX, the genes encoding proteins of the nitrogenase complex. Further, the rhythmic oscillations in exhaust gas CO2 and O2 profiles synchronize faithfully with those in biochemical parameters and gene expression thereby serving as an effective online monitoring tool. These results will have important implications in potential commercial success of nitrogenase‐dependent hydrogen production by cyanobacteria. Biotechnol. Bioeng. 2013; 110:2371–2379. © 2013 Wiley Periodicals, Inc.